2011
DOI: 10.1902/jop.2011.114001
|View full text |Cite
|
Sign up to set email alerts
|

American Academy of Periodontology Statement on the Efficacy of Lasers in the Non‐Surgical Treatment of Inflammatory Periodontal Disease

Abstract: The American Academy of Periodontology (AAP) periodically publishes reports, statements, and guidelines on a variety of topics relevant to periodontics. These papers are developed by an appointed committee of experts, and the documents are reviewed and approved by the AAP Board of Trustees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 19 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…[ 6 20 ] This had also been stated by the American Academy of Periodontology. [ 29 30 ] However, since published reports on the use of diode lasers in periodontal flap surgery are relatively few until date it was decided to evaluate the same. [ 31 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 20 ] This had also been stated by the American Academy of Periodontology. [ 29 30 ] However, since published reports on the use of diode lasers in periodontal flap surgery are relatively few until date it was decided to evaluate the same. [ 31 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…These include the erbium family of lasers (Er YAG, Er YSGG), CO2 lasers, Holmium YAG (Yttrium Aluminum Garnet) laser. Among these, the erbium family has shown considerable promise for the purpose of root modification [22]. …”
Section: Lasers As a Therapeutic Modality For Root Surface Modificationmentioning
confidence: 99%
“…Light from an erbium-doped yttrium, aluminum, and garnet (Er:YAG) laser, which has a wavelength of 2940 nm, is highly absorbed by water and hydroxyapatite to form a micro-explosion, performing the clearance of soft and hard tissues without causing heat damage. [ 6 ] It has been reported that an Er:YAG laser can effectively remove calculus and diseased cementum without thermal damage [ 7 , 8 ] and with good bactericidal effects. [ 9 ] Several studies and 2 systematic meta-analyses have indicated similar outcomes in terms of clinical parameters between Er:YAG laser treatment and SRP in the short term.…”
Section: Introductionmentioning
confidence: 99%